The Tirimbina Biological Reserve, in Costa Rica: model in the conservation of the tropical rain forest, scientific research, ecotourism and environmental education - García-Sánchez, Mariela (2022)
Tirimbina Biological Reserve is a private conservation initiative located in La Virgen de Sarapiquí, Heredia, Costa Rica. Its origins were due to the conservation vision of the American Dr J. Robert Hunter, who, apart from incorporating innovative crops in the area, decided to maintain and encourage the protection of several hectares of tropical forest in the 1960s, and to researchers such as Dr. Allen M. Young who were inspired for the exuberant biodiversity of the tropical forest. Today Tirimbina is in the hands of the Tirimbina Association for Conservation, Research and Education, a Costa Rican non-profit group that is in charge of managing the reserve with a conservation model in which ecotourism generates income not only for the protection of the forest, but to continue financing scientific research and environmental education projects that generate benefits at the local and national levels.